Nitrogen and potassium fertilization of a no-tillage rye-soybean double-cropping system - Ortiz Vega, Rubén Alberto 1958- (Florida : [editor no identificado], 1988)
Tesis (Doctor of Phylosophy)--University of Florida, 1988.
Keywords: ABONOS NITROGENADOS; ABONOS DE POTASIO; COSECHAS -- RENDIMIENTO